Analisis Studi Korelasional Kecerdasan Emosional dan Minat Belajar dengan Hasil Belajar Pendidikan Agama Islam - benny prasetiya (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2019)
This study will analyze the quantitative correlation between emotional intelligence And interest in learning with the learning Results of education of Islam. data analysis was done using statistics: simple and multiple Regression, correlation, partial, and simple plural all. Prior to measurements performed on the significance level a =0.05 testing the hypothesis of the study, first done test requirements analysis includes testing of its homogeneity and normality test. est of the significance of the correlation coefficients obtained from the Model Summary table contained on the first line of the correlation coefficient = 0.421 and F count (F change) = 2.906 with p-value = 0.072 > 0.05. This means that the H0 is rejected. R Square is the coefficient of Determination. The magnitude of R is Square (R2) = 0.177 is 17%. This means that the magnitude of the influence of emotional intelligence and interest in Learning learning outcomes against PAI 17% and other variables that affect the magnitude of the variable results learn PAI is 83%.